2012
DOI: 10.4049/jimmunol.1103616
|View full text |Cite
|
Sign up to set email alerts
|

NK Cell Tolerance to TLR Agonists Mediated by Regulatory T Cells after Polymicrobial Sepsis

Abstract: As sensors of infection, innate immune cells are able to recognize pathogen-associated molecular patterns by receptors such as TLRs. NK cells present in many tissues contribute to inflammatory processes, particularly through the production of IFN-γ. They may display a protective role during infection but also a detrimental role during sterile or infectious systemic inflammatory response syndrome. Nevertheless, the exact status of NK cells during bacterial sepsis and their capacity directly to respond to TLR ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 54 publications
7
56
0
2
Order By: Relevance
“…Interestingly, the direct TLR4 stimulation of NK cells did not improve mortality in our model. These data are in line with two recent studies showing that NK cell reactivity to TLR4 agonist, was reduced in a murine model of sepsis-induced immunosuppression [18] and in humans suffering from sepsis or sterile systemic inflammation [32]. Finally, NK cell hyporeactivity to MPLA could be related to haemorrhage-induced decrease in intracellular TLR4.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, the direct TLR4 stimulation of NK cells did not improve mortality in our model. These data are in line with two recent studies showing that NK cell reactivity to TLR4 agonist, was reduced in a murine model of sepsis-induced immunosuppression [18] and in humans suffering from sepsis or sterile systemic inflammation [32]. Finally, NK cell hyporeactivity to MPLA could be related to haemorrhage-induced decrease in intracellular TLR4.…”
Section: Discussionsupporting
confidence: 79%
“…5a and b). As previously described in NK cells [18], we failed to detect surface expression of TLR4 on NK cells (data not shown), but intracellular TLR4 levels were decreased in the H and HP groups compared with the control (group S, fig. 5c).…”
Section: Mpla-stimulated Dcs Increase Survival In Mice Undergoing Posmentioning
confidence: 60%
“…36,37 We also recently observed that both NK-cell cytotoxicity and IFN-g production were decreased in sepsis, 38 consistent with similar results obtained in mice. 39 Considering the sequence of opposite events that are at work during sepsis, NK cells might have a dual role in sepsis, first contributing to the amplification of the inflammatory response during the early steps of SIRS and then, impaired during CARS and thus participating to its detrimental consequences. 38,40,41 Our data on B7-H6 expression during inflammation provide a novel perspective on the link between microbial infection and NK-cell activation.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon prominently involves the refractoriness of monocytes/macrophages to challenge with LPS or other PAMPs, an observation also known as endotoxin tolerance [34]. Similarly, in murine spleen cells after experimental polymicrobial sepsis and in blood samples from ICU patients (bacterial sepsis or SIRS), IFN-γ production in response to TLR agonists was lost, resembling the tolerance already described for monocytes [13,14]. In concert, NK cell immunosuppression was also observed in blood samples from trauma patients with brain injury, where poor NK cell recruitment into a BCG-induced granuloma model was noticed [35].…”
Section: Natural Mechanisms Restricting Excessive Nk Cell-mediated Inmentioning
confidence: 94%
“…Recently, we have shown that both murine spleen and human blood NK cells express the bacterial sensors TLR2, TLR4 and TLR9 at the protein level and that they are responsive to their agonists in terms of IFN-γ production in the presence of accessory cytokines [13-15]. In contrast to phagocytes, the activation of NK cells by PAMPs often requires complex crosstalk with other immune cells, as already shown with dendritic cells, polymorphonuclear cells, and so on.…”
Section: Systemic Inflammatory Response Syndrome Sepsis and Naturalmentioning
confidence: 99%